What happened and what proves you wrong? Combatting confirmation bias in police investigations through evidence reconstruction and falsification - Sarah Lenz; Tara Zohrevand; Eric Rassin; Bruno Verschuere (PLoS ONE, 2026)
Confirmation bias in criminal investigations has repeatedly been linked to wrongful convictions. Drawing on principles from the Scenario Reconstruction Method, developed for and used in Dutch policing, this study tested whether shifting the investigative focus from identifying suspects to reconstructing scenarios based on available evidence could reduce confirmation bias. In addition, the design included a theoretically motivated manipulation encouraging falsification over verification. The result was a 2 (focus: suspect vs. evidence) × 2 (strategy: verification vs. falsification) factorial online study involving 293 current and future German police officers, who analysed a real wrongful conviction case from the Netherlands. The primary outcome was the accuracy of guilt ratings for the innocent suspect; secondary outcomes assessed the type of proposed next investigative steps. The analyses showed the manipulations had no effect on guilt ratings. However, both strategies did influence investigative reasoning: evidence-focus increased the likelihood of proposing more evidence-based next investigative steps, while falsification-focus promoted more falsification-oriented next investigative steps. Cross-over effects suggested a broader shift in investigative mindset toward more objective reasoning. Future research should explore whether these early improvements in reasoning translate into more accurate outcomes when progressing from brief instructions to multi-stage interventions such as the full Scenario Reconstruction Method.